Thermoresponsive, hydrolytically degradable polymer micelles intended for radionuclide delivery - Hruby, Martin; Konak, Cestmir; Kucka, Jan; Vetrik, Miroslav; Filippov, Sergey K; Vetvicka, David; Mackova, Hana; Karlsson, Goran; Edwards, Katarina; Rihova, Blanka; Ulbrich, Karel (Macromolecular bioscience, 2009)
Novel polymer micelles, prepared by self-assembling thermoresponsive poly(N-isopropylacrylamide)-graft-poly[N-(2-hydroxypropyl)methacrylamide] copolymers with hydrolytically degradable N-glycosylamine groups between the polymer blocks are proposed for delivery of diagnostic and therapeutic radionuclides into solid tumors. The micelles are formed by fast heating of an aqueous solution of the copolymer to 37 degrees C. They have a hydrodynamic diameter of 128 nm (measured using dynamic light scattering) and slowly degrade during incubation in aqueous buffer at pH = 7.4. Labeling with both (131)I and (90)Y proceeds with high yields (>85%). The unlabeled polymers are not cytotoxic for any of the tested murine and human cell lines.
Keywords: nosiče léků; akrylové pryskyřice; Biocompatible Materials; Drug Carriers; akrylamidy; lidé; radionuklidy; micely; Acrylic Resins; biokompatibilní materiály; lékové transportní systémy; Radioisotopes; Acrylamides; Polymers; Humans; Temperature; Micelles; molekulární struktura; Drug Delivery Systems; Hydrolysis; hydrolýza; testování materiálů; polymery; Materials Testing; teplota; Molecular Structure